2015
DOI: 10.21608/ajps.2015.12566
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOCHEMICAL AND BIOLOGICAL STUDY OF (Senecio glaucus subsp. coronopifolius ) (MAIRE) C. ALEXANDER GROWING IN EGYPT

Abstract: Senecio glaucus subsp. coronopifolius (Maire) C. Alexander is wild annual herb distributed in the Egyptian deserts. Total phenolic and flavonoid content of plant root were determined using both HPLC and colorimetric analysis. Syringic acid and hesperidin (1378.802 and 6638.247 mg / 100 gm. dried plant root powder, respectively) were of the highest concentration compounds resulted from HPLC analysis of total phenolic and flavonoid content. The colorimetric estimation of total phenolic and flavonoid content resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Albayrak et al (2014) reported that several species of the Senecio genus growing in Turkey contained high total phenolic contents that ranged from 11.63 ± 2.1 mg GAE/g extract in S. viscosus to 117.45 ± 1.8 mg GAE/g in S. cilicius [ 30 ]. The total phenolic contents for the same species found in Egypt also showed comparable values [ 19 ].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Albayrak et al (2014) reported that several species of the Senecio genus growing in Turkey contained high total phenolic contents that ranged from 11.63 ± 2.1 mg GAE/g extract in S. viscosus to 117.45 ± 1.8 mg GAE/g in S. cilicius [ 30 ]. The total phenolic contents for the same species found in Egypt also showed comparable values [ 19 ].…”
Section: Discussionmentioning
confidence: 82%
“…The results were compared with a recent study which reported that essential oils from S. glaucus exerted a concentration-dependent DPPH scavenging activity [ 38 ]. Furthermore, Mohamed (2015) found that root methyl alcohol extract of S. glaucus growing in Egypt had an antioxidant activity with IC 50 = 79.57 ± 0.74 μ g/ml using the DPPH method [ 19 ]. There were no major differences between our results and the results of other previously reported studies, and this may be due to the presence of the same chemical constituents, including GA and VA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Senecio species are reported to accumulate sesquiterpenoids (eremophilanes, furanoeremophilanes, cacalols, eudesmanes, oplopanes, germacranes, etc.) and pyrrolizidine alkaloids (PAs) [1,8,9], phenolic compounds [10][11][12][13][14][15], and various other secondary metabolites [4,9,16]. Senecio species have been described to possess analgesic [17] and hypoglycemic [18] activity, related to the typical for the genus sesquiterpene lactones, and insecticidal properties [19] related to the presence of PAs.…”
Section: Introductionmentioning
confidence: 99%
“…Senecio species have been described to possess analgesic [17] and hypoglycemic [18] activity, related to the typical for the genus sesquiterpene lactones, and insecticidal properties [19] related to the presence of PAs. Additionally, the taxa are reported to express strong antioxidant, cytotoxic and antimicrobial activity due to the presence of phenolics [11][12][13]15].…”
Section: Introductionmentioning
confidence: 99%